Report of a cereals network: Second meeting, 21-24 April 2008, Foça, Turkey - Maggioni, L.; Katsiotis, A.; Knüpffer, H.; Kleijer, G.; Lipman, E.; Bioversity International; European Cooperative Programme for Plant Genetic Resources (2011)
The second meeting of the Cereals Network took place on 21-24 April 2008 in Foça, Izmir, Turkey. The meeting, organized with the support of the Aegean Agricultural Research Institute (AARI), Menemen, gathered 61 members from 33 countries and a total of 80 participants. The three Cereals Working Groups (Avena, Barley and Wheat) reviewed their progress in the participating countries during Phase VII of ECPGR, focusing on organizational structures, facilities and methods used, description of the collections, germplasm distribution, specific use of accessions, documentation and core collections. They also redefined their priorities for Phase VIII. A number of issues raised by the Working Groups (WGs) will be dealt with jointly at the Network level. Network activities related to Rye, Triticale, Maize and Minor cereals were also discussed, with presentations of invited experts and review of the status of existing ECPGR databases. The Cereals Network demonstrated throughout the meeting that there was significant interest and readiness in taking the AEGIS ideas and principles forward. All WGs agreed that an up-to-date Central Crop Database was a necessary prerequisite for starting the AEGIS process for their respective crops. The Avena WG made steps towards the identification of Most Appropriate Accessions (MAAs) and discussed the methodology to create a European Avena Collection. The Barley WG agreed to start by updating the European Barley Database and discussing criteria for the selection of MAAs. The Wheat WG suggested that genebank managers should start preparing lists of MAAs as potential AEGIS accessions. The participants were also informed about Crop Strategies developed by the Global Crop Diversity Trust and other issues of relevance to genetic resources of cereals. The need to ensure that precise genetic stocks are sustainably maintained was brought into the discussions from the Crop Strategies on Wheat, Barley and Oats. Emphasis was also put on pre-breeding, specifically targeting climate change and plant responses to biotic and abiotic stresses, but also the nutritional value of crops.